Ponto de murcha permanente do feijoeiro cultivado em Latossolo e Nitossolo vermelhos - Salvestro, Alexandre de Castro (2010)
The permanent wilting point (PWP), determined for the cultivation of beans in Paleudult and Haplorthox according to the state of the water in the soil in terms of quantity and potential energy, through interferences related to texture classes, depth and methods of quantification occurs as a result of the movement of the water for a potential difference, restricting the quantity of water available to the plant, reflecting in its photosynthesis and consequently in the production. However, as the matric potential varies in different soils along the profile, the PWP must be determined for each situation, in order to study the the response of the plant to the water potential in the soil. Therefore, the laboratory definition of water available to the plants (with deformed or undeformed samples), stands the chance of serious mistakes, indicating that the limits of water availability to the plants must also be carried out by the physiological method, considering the conditions of soil and cultivation. In this study, the permanent wilting point measured by the physiological method for the Paleudult and Haplorthox in the cultivation of beans to a soil humidity in which the plant is unable to extract more from 0,186 m3 m-3 and 0,083 m3 m-3, the depths (0-15 cm) respectively, besides, the respective soils the photosynthetic rates reached the zero limit of CO2 assimilation of the plant in the exact general average of PWP of 0,187 m3 m-3, for Paleudult and the zero limit of assimilation of CO2 of the plant, before the permanent wilting point average of 0,082 m3 m-3 for the Haplorthox.